IoT Technology is Benefiting Today’s Modern Farming Industry - Shankar, R; Duraisamy, S (International Journal of Computer Sciences and Engineering, 2025)
Agriculture plays very important role in the development of agricultural country. In India about 75% of population depends upon farming and one third of the nation’s capital comes from farming. Issues concerning agriculture have been always hindering the development of the country. The only solution to this problem is smart agriculture by modernizing the current conventional methods of agriculture. To improve efficiency, productivity, global market and to reduce human intervention, time and cost there is a need to divert towards new technology named Internet of Things. It is the network of devices to transmit the information without human involvement. IoT works in synergy with agriculture to obtain smart farming. This paper focuses on major role of IoT in agriculture that leads to smart farming industry